A longitudinal study of hepatitis B surface antibody level after the accelerated vaccination protocol applied to health workers in a hospital of Thailand - Naesinee Chaiear; Phanumas Krisorn; Chanida Seehamoke (Elsevier, 2023)
Background: Hepatitis B infection persists in Thailand, especially among health personnel. The current immunization protocol (3 doses in 6 months) is too slow to protect against infection; thus, an accelerated protocol has been in place as the accelerated protocol at a supra-tertiary hospital since 2014. Aim: To measure the anti-HBs level 1, 2, and 5 years post-accelerated vaccination of health personnel who had received the hepatitis vaccine using. Methods: A descriptive study was conducted. Electrochemiluminescence Immunoassay; ECLIA (Roche Diagnostic Cobas 6000, Indianapolis, IN) was used to measure the anti-HB level 1, 2, and 5 years after the third dose in 73, 58, and 20 participants, respectively. Findings: The starting group number declined over time as workers resigned or transferred away, so the tested number in years 2 and 5 represents the remaining workers that started the study in year 1. The respective geometric mean titer after 1, 2, and 5 years was 1765.8, 164.7, and 107.9 mIU/mL. Fifty-four participants (93.1%) had lower antibody levels in the second year than in the first year. Nine participants (45.0%) had lower antibody levels in the fifth year than in the second year. Conclusion: The anti-HBs level declined from the first to the second and fifth years; however, the anti-HBs level persisted at a protective level. The accelerated protocol benefited health personnel, protecting them from hepatitis B infection.